Impact of age on EGFR mutations in never-smoking female lung adenocarcinoma patients with malignant pleural effusion - Wu, Qian (Int J Clin Exp Pathol, 2018)
Our aim was to evaluate EGFR mutations in never-smoking female lung adenocarcinoma patients with malignant pleural effusion and to reveal the relationship between age and EGFR mutations. Never-smoking female lung adenocarcinoma patients were retrospectively studied, including 301 biopsy samples and 80 cytological specimens. Our results showed a significant increase of EGFR mutation prevalence by increase of age in cytological specimens, but not in biopsy samples. Our data suggests that age at the time of diagnosis may be associated with presence of EGFR mutations in patients with malignant pleural effusion.